AAGBS hosts Cardiff University delegates for strategic academic collaboration - UiTM, AAGBS (Arshad Ayub Graduate Business School (AAGBS), 2024)
AAGBS Welcomes Cardiff University Delegates! The faculty is thrilled to host esteemed delegates from Cardiff University, Wales, United Kingdom, at the Arshad Ayub Graduate Business School (AAGBS) after their visit at UiTM's Vice Chancellor's office. They're here for an engaging discussion and collaboration with faculties from UiTM. The delegates are conducting further discussions on exciting academic initiatives and partnerships with faculties from the Faculty of Business and Management, College of Creative Arts, Faculty of Law, Faculty of Computer and Mathematical Sciences, College of Engineering, and Arshad Ayub Graduate Business School. The discussion brings a sense of excitement as the potential joint activities would help shape the future of education and research.